Hydraulic Erosion Rate of Reinforced Tailings: Laboratory Investigation and Prediction Model - Xuanyi Chen; Xiaofei Jing; Hai Cai; Yijun Wang; Luhua Ye (Advances in Materials Science and Engineering)
Tailings dams are high-potential-energy dams built to store various ore tailings, and the overtopping failure caused by hydraulic erosion is one of the most common failure modes. The characteristics of hydraulic erosion of the reinforced tailings were studied by using the self-made erosion apparatus with four kinds of reinforcement spacing 2.5, 1.7, 1.3, and 1.0 cm, respectively. The test results show a positive correlation between the reinforcement spacing and erosion rate of tailings. Based on the sediment scouring theory, the scouring constant in the erosion rate formula is determined to be 0.056 mm/s; a prediction model for the hydraulic erosion rate of reinforced tailings is established by introducing the collapse coefficient into the results of the overflow test of reinforced tailings. This model can provide a reference for the prediction of overtopping-induced erosion failure of the reinforced tailings dam.